Role of blood flow in endothelial functionality: a review - Zhou, Hui Lin; Jiang, Xi Zhuo; Ventikos, Yiannis (Frontiers in Cell and Developmental Biology, 2023)
Endothelial cells, located on the surface of blood vessel walls, are constantly stimulated by mechanical forces from the blood flow. The mechanical forces, i.e., fluid shear stress, induced by the blood flow play a pivotal role in controlling multiple physiological processes at the endothelium and in regulating various pathways that maintain homeostasis and vascular function. In this review, research looking at different blood fluid patterns and fluid shear stress in the circulation system is summarized, together with the interactions between the blood flow and the endothelial cells. This review also highlights the flow profile as a response to the configurational changes of the endothelial glycocalyx, which is less revisited in previous reviews. The role of endothelial glycocalyx in maintaining endothelium health and the strategies for the restoration of damaged endothelial glycocalyx are discussed from the perspective of the fluid shear stress. This review provides a new perspective regarding our understanding of the role that blood flow plays in regulating endothelial functionality.